UPAYA PENINGKATAN PENJUALAN PRODUK PERAWATAN KULIT : PENGADOPSIAN STRATEGI VIRAL MARKETING - Riza Safira Nurulita; Ignatius Hari Santoso (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Differences in marketing tools due to technological developments allow marketers to customize and use digital platforms, one of which is using of viral marketing strategies. This study confirms the role of viral marketing strategies in Azarine's skincare product purchase intentions and attempts to measure the effectiveness of these strategies on sales. By using 100 respondents spread across different cities in Indonesia via social media, the results proved that viral marketing strategies divided into messenger, messages and environments, can be significant predictors of consumer’s purchase intention. The relationship between the designs was tested by SmartPLS4 with the path analysis technique, showed that increased interaction and product engagement generated interest in purchases and effectively increased sales in the short term